Current approaches to selecting patients for heart transplantation - M. Sh. Khubutia; S. R. Gilyarevsky; V. V. Sokolov; E. V. Kovaleva; I. M. Kuzmina; E. I. Boichevskaya (Трансплантология (Москва), 2018)
The paper analyzes current approaches to selecting heart transplantation (HT) recipients, namely, approaches to assessing the severity of heart failure since the latter is the most common indication for HT. The approaches to selecting patients will be refined as the availability of new types of therapy increases and the implantation of mechanical extracorporeal circulation devices is ranked as a more standard intervention. With allowance made for the shortage of donor organs, it is anticipated that the trend in the performance of HT will persist in the most critically ill patients who need long-term parenteral use of positive inotropic drugs and mechanical circulation support.